Comparison of Selected Journal Quality Indicators of Analytical Chemistry Journals - Ahmad, Akil; Ahmad, Shakil; Waris, Abu; Abdel-Magid, Isam Mohammed (Journal of Information and Knowledge, 2017)
Aim of this research study is to predict the correlation, if any, between the journal impact factor, SCImago ranking, Eigenfactor score and H-index of Analytical chemistry journals and quality of these journals. JIF is considered a good parameter for evaluation of scientific journals but has been criticized on many counts such as self-citation, limitation to English language etc. Seventy five (75) analytical chemistry journals indexed in WoS and Scopus databases were selected in this research for comparison of various indices. Correlations between indices (JIF, ES, SJR, and H-index) were evaluated using Pearson and Spearson’s correlation. Annual Review of Analytical Chemistry was at the top with JIF of 8.0 and the lowest for American Laboratory journal with JIF of 0.028. In case of SCImago ranking, Eigenfactor score and H-index, highest valued journals were reported as Annual Review of Analytical Chemistry (SJR = 3.078), Analytical Chemistry (ES = 0.1588) and Analytical Chemistry (H-index = 109). Lowest valued journals were reported as American Laboratory journal (SJR = 0.106), Archeosciences-Revue D Archeometrie (ES = 0.0001) and Instrumentation Science and Technology (H-index = 0). Throughout the study, none of the journals had the same ranking to compare different indicators. Pearson’s correlation between JIF and SJR values reached a high value (0.936) as compared to either ES (0.558) or H5 (0.567).